The Effect of Mind Simulation Method on Reducing Stuttering and Communication Attitude - Hamid Kamarzarin; Zahra Fallahi; Maryam Tehranizadeh (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Fluency disorder or stuttering is a Speech disorder in humans whose prevalence is higher at the ages before puberty. Mind simulation may be effective in reducing the severity of stuttering and some associated problems such as negative attitude towards communication. Therefore, this study aims to investigate the effect of mind simulation method on reducing stuttering and improving communication attitude in children and adolescents with stuttering aged 7-16 years.Methods This is a quasi-experimental study with a pre-test/post-test/follow-up design. Participants were 30 children and adolescents with stuttering aged 7-16 years (9 females and 21 males) referred to a psychology clinic in 2020. They completed DeNil and Brutten's communication attitude test-revised (CAT-R) and Riley's Stuttering Severity Instrument- 4(SSI-4) in the pre-test stage. Then, they underwent treatment by the Mind Simulation method for three months. Immediately after and one month after treatment, they completed the CAT-R and SSI-4 questionnaires again. Repeated Measure Analysis of Variance and Friedman Test were used to analyze the collected data.Results There was a significant difference between pre-test, post-test, and follow-up phases in stuttering severity (P=0.0001) and communication attitude (P=0.0001). The severity of stuttering decreased in the post-test and follow-up phases compared to the pre-test phase, while communication attitude improved in the post-test phase compared to the pre-test phaseConclusion The mind simulation method can reduce stuttering and improve communication attitude in children and adolescents with stuttering.